A qualitative study of family members' experiences of their loved one developing dementia and their subsequent placement in a nursing home. (7th February 2021) - Fekonja, Zvonka; Kmetec, Sergej; Novak, Barbara; McCormack, Brendan; Mlinar Reljić, Nataša
Abstract: Aim: To investigate the family members' experiences with receiving help and support while their loved one develops dementia and their subsequent placement in nursing homes. Background: As the dementia disease progresses, some family members will struggle with the option of nursing home placement. This situation can precipitate feelings of anger, disappointment and guilt, all of which can be overwhelming. Methods: A qualitative descriptive study with in‐depth interviews ( n = 19) was carried out in several nursing homes of Slovenia's North Eastern Region. Results: Inductive thematic analysis identified two main themes: (i) developing the diagnosis and (ii) accommodation process. Family members noticed the progressive behavioural changes in their loved ones. While they were searching for help at the primary health care level, they experienced a lack of help and support. Conclusions: When family members detect behavioural changes in their loved ones, the primary health care team should establish an early diagnosis of dementia and provide adequate decision‐making support. Implications for Nursing Management: The findings are useful to prepare guidance for a family member to inform them of the types of support available and from which associations and organisations. To achieve adequate management support, primary health care teams need to be aware of family member experiences.